1996
DOI: 10.1182/blood.v88.4.1306.bloodjournal8841306
|View full text |Cite
|
Sign up to set email alerts
|

Association of smooth muscle cell tissue factor with caveolae

Abstract: There is still no satisfactory explanation for the low catalytic activity of tissue factor (TF)/factor VII(a) complexes towards coagulation factor X, as found on the apical surface side of cell layers. It has been hypothesized that TF exists in a latent form. Layers of cultured human smooth muscle cells, constitutively expressing TF, were immunogold-labeled for TF in situ and processed for electron microscopy. We showed that, besides internalization and accumulation in lysosomal-like structures, TF remained as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Moreover, Mulder et al . () utilized immunogold‐labelling to locate TF in intracellular lysosome‐like structures that exhibited high morphological resemblance to MVBs with intraluminal exosomes. Thus these data suggest that TF can be loaded into exosomes originating from VSMC MVBs.…”
Section: Exosomes Released From Vascular Smooth Cells Mediate Calcifimentioning
confidence: 99%
“…Moreover, Mulder et al . () utilized immunogold‐labelling to locate TF in intracellular lysosome‐like structures that exhibited high morphological resemblance to MVBs with intraluminal exosomes. Thus these data suggest that TF can be loaded into exosomes originating from VSMC MVBs.…”
Section: Exosomes Released From Vascular Smooth Cells Mediate Calcifimentioning
confidence: 99%
“…Ultrastructural localization of TF in a variety of cell types showed that a fraction of the TF in these cells is associated with caveolae, a specialized membrane domain rich in cholesterol-and sphingolipid-rich rafts. [84][85][86][87]. Mulder et al [84] speculated that the caveolae-associated TF represents the encrypted form, which can rapidly be activated at sites in which vessel wall integrity is lost.…”
Section: (V) Protein Disulfide Isomerase: Regulation Of Tf Activity Bmentioning
confidence: 99%
“…It has been reported that TF exists in the cell membrane of smooth muscle cells inside invaginations or caveolae. 23 This encrypted TF is suggested to be a latent pool of coagulant TF. If this were indeed the mechanism of encryption, it could explain the activation of TF after lysis or freeze-thawing in the previous study, for this would open up these caveolae and expose the hidden TF.…”
Section: Encrypted Tfmentioning
confidence: 99%